(untitled) (Archives of Criminology, 2018)
The aim of the research presented in the article is to show the amount, structureand dynamics of the offences against life and health that are defined in Chapter XIXof the Polish Penal Code 1997. The article offers an analysis of the data on the of fencesagainst life and health based on the publicly available statistics for the years 1999–2016.In the analysed period, two main trends relating to the amount of crime shouldbe identified. The first, encompassing the years 1999 to 2003, was an upward trend,followed by a downward trend that accelerated in the second decade of this century.In fact, since 2011 there has been a general, spectacular and significant drop of crimein Poland, also including offences against life and health.For the purpose of the analysis, offences against life and health are divided intofour main categories: homicide, assault or battery, bodily injury and other crimes(not included in the above-mentioned categories). Based on the offences recorded bythe police in the years 1999–2003, the number of all offences against life and healthexceeded 35,000 in 2003. Then, the number of such offences was relatively stable (about31,000-32,000 per year) and has decreased to about 18,000 since 2011.Generally, over the analysed period, the number of offences in three of four catego -ries: homicide, assault and battery and bodily injuries, has shrunk several times. The onlyexception to the general trend relates to the offences under Art. 160 of Criminal Code(defined as “exposing a human being to an immediate danger of loss of life or bodilyinjury or impairment of health”) that is invoked, among others, in cases of parentalneglect, distribution of designer drugs or even as allegations of medical malpractice.The significant drop in crime during the second decade of the 21st century asksfor an explanation. The first possible reason for this is that a crime drop has beenobserved in many countries, seems to be a common and international phenomenonand, as such, it also applies to Poland. The second explanation, probably the mostimportant one, is that the crime drop in Poland has been due to the systemic changesin the recording of crimes.First of all, in 2013 a new police information system was introduced, which led tosome problems with making it compatible with the old one. In parallel, in the same year,a substantial change in the recording of juvenile delinquency was adopted. Accordingto the new methodology, offences committed by juveniles are recorded by the policeonly after juvenile courts confirm the fact that a juvenile has indeed committed a crime.The problem is that there is no rule that would oblige juvenile courts to give suchinformation back to the police. It could possibly have a strong impact on the statisticsof crime, especially regarding assault and battery and bodily injuries, as juveniles usedto be a significant group of individuals suspected of such crimes. To make it clear,the data about ascertained crimes in Poland do not include punishable acts committedby juveniles.Furthermore, the investigation and proceedings carried out by the prosecutor’soffices and entrusted to other competent bodies than the police are not includedin the official police data. It all means that, since 2013, the range of the police data hasbeen substantially limited and does not reflect incidence of crime in full.The third possible reason for the falling number of crimes is the effect of thedemographic processes. It should also be taken into account that the populationof adolescents in Poland is currently at the lowest level since World War II.The article discusses four main categories of the offences covered by Chapter XIXof the Penal Code.The category “Homicide” is not a simple one. It includes manslaughter (Art. 148§ 1), murder (Art. 148 § 2 describes different forms of such felony: killing withparticular cruelty, in connection with hostage taking, rape or robbery, for motivesdeserving particular reprobation, and also with the use of explosives). The PolishCriminal Code also has provisions relating to heat of passion manslaughter justifiedby the circumstances (Art. 148 § 4 of the Penal Code). According to the data recordingby the police, in the analysed period the number of homicide cases has decreased bymore than 50%!“Bodily injury” is a very broad category that also covers causing serious bodilyharm, which includes, among others, deprivation of sight, hearing, speech or the ability to procreate, or inflicting a serious crippling injury, an incurable or prolonged illness,an illness dangerous to life, a permanent mental illness, a permanent total or substantialincapacity to work in an occupation, or a permanent serious bodily disfigurementor deformation (Art. 156 § 1 of the Penal Code), stipulating a heavier penalty if theconsequence of an act is death (Art. 156 § 3 of the Penal Code) than for causinga bodily injury or an impairment to health other than specified in Art. 156 Penal Code(Art. 157 § 1 of the Penal Code). If the bodily injury or an impairment of health doesnot last longer than seven days, prosecution will be brought on a private charge. Overthe analysed period, most of these cases were qualified under Art. 157 of the PenalCode. The total number of bodily injuries has been slowly decreasing over the analysedperiod, reaching about 60% of the initial amount.“Assault and battery” (Ar. 158 and Art. 159 of the Penal Code) is also a verybroad category and includes brawling (the perpetrator who participates in a brawlis responsible for the complicity in the act that means an immediate danger to life ormay lead to a bodily injury) and battery, when the role of the victims and the offendersare clearly determined. Since 2011, the police data have shown a spectacular dropin the number of assault and battery – to one third of previously recorded cases. It isundoubtedly a side effect of the change in the algorithm of recording punishable actscommitted by juveniles.The conclusion is that the changes in the methodology of recording ascertainedcrime by the police have limited the range of available data on crime. Therefore, interpretingthe data on offences against life and health has now been made more difficult asthe punishable acts of juveniles are no longer included in the police information system.In such a situation, possible ways of gathering data on crime and their interpretation should be reconsidered.Moreover, there is an urgent need to develop and conduct criminological researchon offences against life and health.